Mathematic simulation of vibrations electric locomotives ChS4 - Reidemeister, O. H.; Snitko, M. P. (Science and Transport Progress, 2012)
The article describes the model of vibrations of an electric locomotive ChS4. A vehicle is considered as a mechanical system of 9 rigid bodies (a body, 2 bogie frames, 6 wheelsets).